Role of the Air-Blood Barrier Phenotype in Lung Oxygen Uptake and Control of Extravascular Water - Miserocchi, Giuseppe; Beretta, Egidio; Rivolta, Ilaria; Bartesaghi, Manuela (Frontiers in Physiology, 2022)
The air blood barrier phenotype can be reasonably described by the ratio of lung capillary blood volume to the diffusion capacity of the alveolar membrane (Vc/Dm) which can be determined at rest in normoxia. The distribution of the Vc/Dm ratio in the population is normal; Vc/Dm shifts from ~1, reflecting a higher number of alveoli of smaller radius providing a high alveolar surface and a limited extension of the capillary network, to just opposite features on increasing Vc/Dm up to ~ 6. We studied the kinetics of alveolar-capillary equilibration on exposure to edemagenic conditions (work at ~ 60% maximum aerobic power) in hypoxia (PIO2 90 mmHg), based on an estimate of time constant of equilibration (τ) and blood capillary transit time (Tt). A shunt-like effect was described for subjects having a high Vc/Dm ratio reflecting a longer τ (> 0.5 s) and a shorter Tt (< 0.8 s) due to pulmonary vasoconstriction and a larger increase in cardiac output (> 3-fold). The tendency to develop lung edema in edemagenic conditions (work in hypoxia) was found to be directly proportional to the value of Vc/Dm as suggested by an estimate of the mechanical properties of the respiratory system with the forced frequency oscillation technique.